Transforming Institutional Credit Hour Loads to Address Curriculum Structural Rigidity Based on Interdisciplinary Competencies - Ariyanto Siahaan (AMUYA: JOURNAL OF MANAGEMENT, 2026)
The primary challenge in religious higher education is the dominance of static core theology curricula, which creates an excessive burden of mandatory institutional credit hours. This condition results in curriculum structural rigidity that restricts students' acquisition of interdisciplinary competencies. This policy methodology employs a descriptive qualitative approach, utilizing the Urgency, Seriousness, and Growth (USG) method for issue prioritization and William N. Dunn’s criteria for policy alternative evaluation. The analysis reveals that the current curriculum structure lacks sufficient flexibility for students to adapt to modern workforce dynamics. The discussion emphasizes that transforming credit hour loads is a crucial step for the effective implementation of the Merdeka Belajar Kampus Merdeka policy. In conclusion, curriculum restructuring is necessary to dismantle academic rigidity and broaden the graduates' skill spectrum. The primary policy recommendations include adopting Outcome-Based Education (OBE) standards by simplifying mandatory institutional courses, integrating professional competency certifications, and expanding cross-sectoral partnerships. This strategy is expected to produce graduates who are adaptive, competitive, and relevant to cross-industry demands in the digital era.